New film highlights women’s role in protecting the world’s rangelands and pastoral communities - Flintan, Fiona E.; Carleton, Elliot (Land Portal Foundation, 2022)
A recent film(link is external), completed as part of a joint collaboration between the CGIAR Research Program on Livestock(link is external) and CGIAR Research Program on Policies, Institutions and Markets(link is external), highlights the significant role women have in addressing the challenges rangelands face. Titled ‘Reversing, Reviving, Regenerating: Pastoralist women restoring rangelands in Kenya, Kyrgyzstan and Spain’, the film tells the story of three pastoralist women who have taken steps to reverse rangeland degradation and improve rangeland health. Though they come from different parts of the world, they share a common vision–to foster the benefits rangelands can provide for their livelihoods and families as well as for the broader society and environment.